Fetal and Maternal Outcomes of Planned Pregnancy in Patients with Systemic Lupus Erythematosus: A Retrospective Multicenter Study - Dongying Chen; Minxi Lao; Jianyu Zhang; Yanfeng Zhan; Weinian Li; Xiaoyan Cai; Zhongping Zhan (Journal of Immunology Research)
Objective. To investigate the fetal and maternal outcomes as well as predictors of APOs in women with SLE who conceived when the disease was stable, the so-called “planned pregnancy.” Methods. A retrospective multicenter study of 243 patients with SLE who underwent a planned pregnancy was performed. APOs in fetus and mothers were recorded. Results. The average age at conception was 28.9 ± 3.9 years. Duration of SLE prior to pregnancy was 4.4 ± 4.3 years. Fetal APOs occurred in 86 (86/243, 35.4%) patients. Preterm births, intrauterine growth retardation (IUGR), fetal distress, and fetal loss accounted for 22.2%, 14.8%, 11.1%, and 4.9%, respectively. Forty-two preterm infants (42/54, 77.8%) were delivered after the 34th week of gestation. All the preterm infants were viable. Fifty-two patients (52/243, 21.4%) had disease flares, among which 45 cases (45/52, 86.5%) were mild, 6 (6/52, 11.5%) were moderate, and 1 (1/52, 1.9%) was severe. Disease flares were mainly presented as active lupus nephritis (41/52, 78.8%), thrombocytopenia (10/52, 19.2%), and skin/mucosa lesions (9/52, 17.3%). Pregnancy-induced hypertension (PIH) occurred in 29 patients, among which 3 were gestational hypertension and 26 were preeclampsia. Multiple analysis showed that disease flares (OR, 8.1; CI, 3.8–17.2) and anticardiolipin antibody positivity (OR, 7.4; CI, 2.5–21.8) were associated with composite fetal APOs. Conclusion. Planned pregnancy improved fetal and maternal outcomes, presenting as a lower rate of fetal loss, more favorable outcomes for preterm infants, and less severe disease flares during pregnancy.